Estudo do mecanismo antinociceptivo e anti-inflamatório do óleo essencial de Lippia pedunculosa e seu complexo em Β-ciclodextrina - Braga, Renan Marinho (2020)
In most diseases, inflammation and pain are cause and consequence. The most widely used therapeutic classes, non-steroidal anti-inflammatory drugs (NSAIDs) and opioids, have a range of adverse effects that have motivated approaches for the discovery of new drugs. In this context, essential oils and their constituents have emerged as one of the therapeutic alternatives for the treatment of these painful conditions. Lippia pedunculosa essential oil (EOLp) as already reported in the literature presents trypanocidal and amoebicidal effects. However, in experimental models of analgesia and inflammation, these activities need to be further studied. Several approaches are used to improve the pharmaceutical properties of essential oils, including the employment of drug- delivery systems. In this study, we used EOLp/β-cyclodextrin (β -CD) and EOLp alone to evaluate whether the inclusion complex formulation was able to improve the antinociceptive activity of the essential oil in Mus musculus mice. We evaluated the analgesic-like effect of EOLp and EOLp/β-CD in acetic acid- induced abdominal writhes, formalin induced nociception, glutamate, capsaicin and formalin-induced orofacial nociception models and finally we evaluated the anti-inflammatory activity by the carrageenan-induced peritonitis test. EOLp was effective in reducing nociceptive behavior (p<0.05, p < 0.01, and p < 0.001) different from its EOLp/β-CD inclusion complex, which did not change this parameter. Thus, though cyclodextrins are promising as guest molecules hosts, for essential oils rich in peroxide compounds they appear not to be the most promising approach, (at least in terms of analgesic and anti-inflammatory effect). The isolated EOLp yet presented a significant (p<0.05, p < 0.01, and p < 0.001) antinoniceptive effect in the orofacial pain methods and in peritonitis induced by carrageenan, EOLp reduced total leucocyte migration to the peritoneal cavity (p<0.05 or p < 0.01) as well as reducing IL-1β levels in the peritoneal fluid (p < 0.01), which confirmed its anti-inflammatory effect.